Effect of Period of Storage on Physico-chemical Properties and Major Constituents of South Indian Vetiver (Vetiveria zizanioides Linn.) Oil - Dubey, Nidhi; Chhonkar, S. S.; Raghav, C. S. (Indian Forester, 2011)
The physico-chemical properties, chemical composition and odour of South-Indian vetiver oil changes during long term storage. The viscosity, specific gravity, refractive index, combined alcohols, ester value and ester content increased, while transparency, optical rotation. acid value, ester value after acetylation. free alcohols, total alcohols, carbonyl value and solubility (in 80% alcohol) of the stored oil decreased. The odor of the oil gradually improved from green, harsh. woody, earthy, spicy to dry cool, slightly soft woody, balsamic, sweet, and persistent. Among the major constituents of the oil, a continuous increase in the content (%) of -amorphene, -vetivenene and khusimone and continuous decrease in the content of khusimene, -humulene, -longipinene, gurjunene, khusimol and bicyclovetivenol was observed during the storage period from 6 months to 30 months.